2012
DOI: 10.1039/c2an35477b
|View full text |Cite
|
Sign up to set email alerts
|

Raman microspectroscopy of live cells under autophagy-inducing conditions

Abstract: The role of autophagy in numerous physiological responses triggered by a variety of mechanisms both in states of health and disease has raised considerable interest in this cellular process. However, the current analytical tools to study autophagy are either invasive or require genetic manipulation. Raman microspectroscopy is a potentially quantitative analytical method that has been shown to be useful for the label-free, non-destructive analysis of living biological cells and tissues. We present in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…After apoptosis, necrosis or autophagy were induced by defined substances, we were able to identify unambiguously specific clusters for each type of cell death. The spectra of each group showed alterations in their peaks, which were highly specific for apoptosis, necrosis or autophagy . Morphological changes in the cells after treatment with the various drugs supported the induction of the relevant type of cell death (apoptosis, necrosis or autophagy).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…After apoptosis, necrosis or autophagy were induced by defined substances, we were able to identify unambiguously specific clusters for each type of cell death. The spectra of each group showed alterations in their peaks, which were highly specific for apoptosis, necrosis or autophagy . Morphological changes in the cells after treatment with the various drugs supported the induction of the relevant type of cell death (apoptosis, necrosis or autophagy).…”
Section: Discussionmentioning
confidence: 89%
“…The 3‐BrPv treatment group exhibited a decrease in all these peaks. In contrast to cells treated with staurosporine or 3‐BrPv, the resveratrol‐treated cells had less pronounced spectral changes; however, the spectra exhibited a clearly decreased signal at 718/cm (Table ), which is associated with phospholipids and was shown be a useful spectral marker of autophagic response …”
Section: Resultsmentioning
confidence: 99%
“…Using Raman spectroscopy, Konorov et al observed increased phospholipid levels in LMD cells undergoing autophagy due to glutamine depletion. These cells were found to accumulate lipids during autophagy.…”
Section: Resultsmentioning
confidence: 99%
“…Electron microscopy studies have indicated that complete deprivation of serum and amino acids provides a useful model for the further study of cellular autophagy [19] . It is widely accepted that autophagy is induced in several Autophagy induction Autophagy induction Autophagy induction Autophagy induction mTOR-dependent signaling pathway mTOR-dependent signaling pathway mTOR-dependent signaling pathway mTOR-dependent signaling pathway mTOR-independent signaling pathway mTOR-independent signaling pathway mTOR-independent signaling pathway mTOR-independent signaling pathway mTOR-independent signaling pathway mTOR-independent signaling pathway mTOR-dependent signaling pathway mTOR-independent signaling pathway mTOR-independent signaling pathway mTOR-independent signaling pathway [20,21] . Drosophila Rack1, a receptor of activated protein kinase C 1, increases 4.1-to 5.5-fold during nutrient deprivation in all three genotypes.…”
Section: Starvation Inducersmentioning
confidence: 99%